2003
DOI: 10.1002/poc.658
|View full text |Cite
|
Sign up to set email alerts
|

Aromaticity and antiaromaticity: what role do ionic configurations play in delocalization and induction of magnetic properties?

Abstract: epoc ABSTRACT: C m H m (m ¼ 4, 6, 8) species are analyzed in D mh and D (1/2)mh geometries by means of valence bond (VB) calculations. The fundamental factors that distinguish aromatic and antiaromatic modes of electron delocalization are elucidated by analysis of the mixing between the covalent-state and ionic structures that distribute the electrons in all possible modes available in the cycle. The major difference found is that, by contrast to the aromatic species where all the ionic structures mix into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
43
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 89 publications
3
43
0
Order By: Relevance
“…These results contradict an earlier comparison [23], which however only took concerted six-electron movements in account. The importance of ionic structures is in good agreement with the results by Shurki et al [24] for the same direction movement. In general, the role of the ionic spin structures is, however, not qualitatively different from the role of the ionic structure in H 2 , since the dominant opposite direction movement is much less affected by the restriction to covalent structures.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…These results contradict an earlier comparison [23], which however only took concerted six-electron movements in account. The importance of ionic structures is in good agreement with the results by Shurki et al [24] for the same direction movement. In general, the role of the ionic spin structures is, however, not qualitatively different from the role of the ionic structure in H 2 , since the dominant opposite direction movement is much less affected by the restriction to covalent structures.…”
supporting
confidence: 91%
“…In order to explore delocalization, the maximum probability paths connecting these structures thus have to be investigated. This is somewhat analogous to work by Shurki et al [24] and seemingly related to the concept of diamagnetic ring currents [20,3]. However, like Maynau and Malrieu [23] we do not restrict our search to paths, where all electrons move in the same circular direction (Fig.…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…D, E & F in Chart 1) is avoided as much as possible and this is consistent with retaining a high degree of aromaticity. 64 Roberts and Szwarc reported bond dissociation energies of 75.5, 76.5, and 77.5 kcal/mol, respectively, for α-, βand γ-picoline, respectively, 65 relative to the bond dissociation energy of toluene which was ΔH 298 = 77.5 kcal/mol in 1948. Using ΔH 298 = 89.6 kcal/mol for the bond dissociation energy of toluene, Kromkin et al 62 reported bond dissociation energies for α-, βand γ-picoline of 87.2, 90.4, and 86.5 kcal/mol, respectively, and of 86.0 kcal/mol for 4-methyl-quinoline (4MQ).…”
Section: Point Of Reference: Benzyl Radical and Benzoannulationmentioning
confidence: 99%